“One does not always think that it`s always present” : a case study of employee involvement in CSR - Kuvaja, Eveliina (2019)
According to micro-CSR studies individual stakeholder reactions to corporate social re-sponsibility (CSR) can explain the variability between CSR activities and organization`s financial performance (Jones et al., 2017). Therefore, studying and understanding stake-holder perspectives on CSR is needed. This case work focuses on one specific stakeholder group, namely employees and their involvement in CSR. Employee involvement in CSR is necessary for strategy implementation, but it is also beneficial, since involvement can improve organization reputation (De Roeck et al., 2016) and lead to additional organiza-tional outcomes, such as higher employee commitment (Kim et al., 2010). This work aims to examine employee current involvement in CSR as a case study in large multinational corporation. The aim with this work is to help organization in its CSR strategy implementation by describing the current involvement of employees and giving recommendations how involvement could be further supported. This qualitative study is based on the theoretical background considering the relationship between employees and CSR and empirical data consisting of five focus group interviews conducted within the employees of the case organization. The results of the work indicate that employees as a group are comprehensively involved in CSR. Comprehensive CSR rise emotions and is connected to organizational commitment, which is found to be mediated from organizational identification. As a group employee involvement is comprehensive, which is based on the tripartite role of employees and variability in individual perceptions and experiences of CSR. Employees as a group see that CSR is present comprehensively, even though they do not actively think about it. Comprehensiveness of employee involvement may be a challenge, since in order to sup-port involvement, CSR work need to be consistent and be communicated consistently between different segments and dimensions for different kind of individuals. Overall this work recommends case organization to take the full benefits out of its comprehensive CSR work, which employees of the organization seem to value. This work suggests organization to translate CSR strategy to employees in interaction with CSR, HRM and communicational professionals and employees themselves.